The Influence Of Informal Residential Constructions On The Urban Image Of A Sector In Northern Peru - Ramirez, Eduardo Edson Salcedo; Carreño, Abner Josue Escobar; Ayala, Samantha Aymee More; Arellano, Pamela del Carmen Castellano (Migration Letters, 2024)
The study was carried out in the El Molino sector of the district of Trujillo, in northern Peru. It investigated the impact of informal residential constructions on the urban image of the sector. The research approach, type and design were quantitative, applied and non-experimental; of cross-sectional and correlational scope. The unit of analysis was the workers of the Provincial Municipality of Trujillo, including as a sample 30 technical workers belonging to the Urban Development Management, to whom two questionnaires were applied after meeting the criteria of validity and reliability. The results were presented in interpreted tables, showing that 60% of the informal residential buildings have an average level and 66.7% have a regular level with respect to urban image. The study establishes that there is an inverse influence between informal residential constructions and urban image, based on the coefficient Rho= -0.726 and a significance p<1%; likewise, it was determined that the behavior of the urban image variable was explained 89.5% by the informal constructions variable and 10.5% by other causes.